Common sports-related hand injuries. Issue 7 (July 2014) - Jackson, Thomas; Mahoney, Melissa; Oliveira, Miguel
Hand injuries caused by participation in sport are a common presentation to general practice. These injuries, which are seen in a wide age range of patients, are often isolated problems that may lead to significant morbidity. This article aims to outline the management of a broad spectrum of hand injuries to enable appropriate management in primary care or suitable referral to specialist services.